We have to find y such that sin y = cos 3y.

We know that sin(y) = cos(pi/2-y),so we can convert the given equation to:

sin(y) = cos(pi/2-y) = cos(3y)

We now equate pi/2 - y and 3y

pi/2 - y = 3y

=> pi/2 = 3y + y

=> 4y = pi/2

=> y = pi/8

**Therefore y = pi/8 + 2*n*pi**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now